16.3: True‐Color 640 ppi OLED Arrays Patterned by CA i‐line Photolithography. Issue 1 (June 2015) - Malinowski, Paweł E.; Ke, TungHuei; Nakamura, Atsushi; Chang, Ting‐Yu; Gokhale, Pritesh; Steudel, Sören; Janssen, Dimitri; Kamochi, Yoshitaka; Koyama, Ichiro; Iwai, Yu; Heremans, Paul
Abstract : In this paper, side‐by‐side patterning of red, green and blue OLEDs is demonstrated. To achieve 640 ppi arrays with 20 µm subpixel pitch, chemically amplified, i‐line photoresist system with submicron resolution was used. These results show feasibility of obtaining full‐color displays with ultra‐high resolution.